Characterization of Submicron Oil Mist Particles Generated by Metal Machining Processes - Moriaki Iwasaki; Kojiro Hirai; Kanta Fukumori; Hidenori Higashi; Yayoi Inomata; Takafumi Seto (Aerosol and Air Quality Research)
Abstract The number size distributions of submicron oil mist particles generated by three industrial metal (steel) machining processes—lathe machining, cutting, and grinding—were measured using an electrical mobility analyzer and an optical particle spectrometer. The measured number concentration of ultrafine particles (UFP; ~30 nm diameter) reached 107 particles cm−3 during each machining process. The condensation of thermally evaporated oil vapor was considered to be a major route of ultrafine particle generation during lathe machining and grinding, which used an oil-in-water emulsion and an insoluble lubricant oil, respectively. Cutting, which did not use lubricant oil, also produced a steep increase in the number concentration of UFP; these particles may have formed from residual oil-in-water emulsion on the surface of the workpiece after lathe machining. A simplified numerical simulation was used to quantify the particles arising from machining and leakage when the apparatus was opened. Although local ventilation effectively reduced the concentration of the oil mist in the apparatus and prevented the diffusion of this substance when the apparatus door was opened, leakage was observed when the workpieces were exchanged; this leakage was attributed to entrained particles on the workpieces. Hence, countermeasures to prevent entrained oil mist are necessary to improve the air quality in working environments.